Brain Radiation-Related Black Dots on Susceptibility-Weighted Imaging. Issue 4 (August 2014) - Varon, Daniel; Simons, Michael; Chiang, Francisco; Tedesqui, Gustavo; Pacheco, Gerardo; Martinez, Pablo; Castillo, Mauricio
Small blood vessel injury is a feature of post irradiation brain. Susceptibility weighted imaging (SWI) is a technique that exploits the magnetic properties of tissues, such as blood and iron content and is thus sensitive to hemorrhage as a marker of small vessel injury. Our purpose was to assess post irradiation brain findings using SWI. We evaluated 12 patients with follow-up MRI studies who underwent cranial irradiation for primary or metastatic tumors. From their clinical records, the latency interval, type of radiation, and total dose were established. The number and the distribution of "black dots" on SWI were analyzed. We also compared the findings on SWI with those seen on other MRI sequences. In all patients, black dots were clearly identified on SWI, while on conventional MRI (T2 and FLAIR) none were visible. Two patients with glial tumors received radiation with fields conforming to tumor beds, while all other patients received whole brain irradiation or craniospinal radiation. The total radiation doses ranged from 45–54 Gy. Latency interval between the time of irradiation and time of detection of the black dots was four to 60 months (mean, 31 months). In ten patients diffuse black dots were observed and in two patients these were located in the irradiated field. Black dots occurred in the cerebrum, cerebellum, and choroid plexuses. None of these dots showed enhancement. Follow-up in four patients showed that the numbers of these black dots had increased. Black dots were not present before radiation in any patient. Radiation-related black dots are an effect of cranial irradiation and may be related to small vessel damage. SWI is a sensitive technique for evaluation of these black dots.